THE IMPORTANCE OF AGRICULTURAL PRODUCTION AND VARIATION OF BACTERIAL MICROFLOWER ON THE QUALITY OF POULTRY MEAT IN VARIOUS MARKETING CONDITIONS - Rita GOLBAN; Artur GOLBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The scientific research reflected in this investigation had the purpose to study the importance of agricultural production and the variation of bacterial microflora on the quality of certain categories of poultry meat in different commercial conditions. In the scientific paper were analysed the indices of the volume of agricultural production in different categories of households during the last period and highlighted the aspects of its increase and decrease. In the same time, by laboratory microbiological methods were evaluated the results of the saprophytic and pathogenic microflora of three categories of poultry meat under various commercialization conditions. The results of the study confirmed that all categories of commercialized poultry meat showed an insignificant number of coccic microorganisms both in the surface layers and in the depth of the meat, which corresponds with the commercialization requirements and is acceptable in human food.